Ruthenium-based catalyst as well as preparation method and application thereof
By modifying the support titanium dioxide to support precious metal components and regulating the electron transfer process, a highly active ruthenium-based catalyst was prepared, which solved the problem of wide distribution of product in Fischer-Tropsch synthesis reaction and achieved the improvement of Fischer-Tropsch synthesis activity and selectivity.
Patent Information
- Application Number
- CN202310702659.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-13
AI Technical Summary
The carbon chain growth of the ruthenium-based catalyst in Fischer-Tropsch synthesis reaction follows the polymerization mechanism, and the products are mainly linear hydrocarbons, making it difficult to obtain the target product with high selectivity, which limits the efficient conversion and utilization of synthesis gas.
The modified carrier titanium dioxide loads precious metal components, and the oxygen vacancies and trivalent titanium distribution on the carrier are regulated by calcining and alcohol washing in a reducing atmosphere, changing the metal-carrier electron transfer process, and further loading ruthenium elements to prepare high activity and highly selective ruthenium-based catalysts.
The activity of Fischer Tropsch synthesis reaction and the selectivity of target products are significantly improved, and the CO conversion rate and heavy hydrocarbon selectivity are improved.
Smart Images

Figure CN119114062A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a ruthenium-based catalyst and a preparation method and application thereof. Background Art
[0002] The Fischer-Tropsch synthesis reaction can catalytically convert synthesis gas (carbon monoxide and hydrogen) produced from non-petroleum-based carbon resources such as coal, natural gas, and biomass into liquid fuels and high-value-added chemicals, which can effectively alleviate the contradiction between oil supply and demand and provide security for the national energy strategy. However, since the carbon chain growth on ruthenium-based catalysts obeys the polymerization mechanism, the products are mainly straight-chain hydrocarbons with a wide distribution range and obey the Anderson-Schulz-Flory distribution law. It is difficult to directly obtain the target product with high selectivity, which seriously restricts the efficient conversion and utilization of synthesis gas. Therefore, one of the keys in the Fischer-Tropsch synthesis reaction is to achieve the regulation of the distribution of Fischer-Tropsch synthesis products by adjusting the structural properties of the catalyst, thereby improving the selectivity of the target product.
[0003] The active components of Fischer-Tropsch synthesis are mainly iron, cobalt and ruthenium. Among them, supported ruthenium-based catalysts have been widely studied due to their excellent activity, excellent chain growth ability and high stability. Generally, the size effect, metal-support interaction, additive effect and support effect of ruthenium can be regulated to regulate the activity and selectivity of the catalyst. Huang Yanqiang and others from the Dalian Institute of Chemical Physics of the Chinese Academy of Sciences regulated the size of ruthenium particles by changing the amount of ruthenium precursor in the impregnation method, thereby changing the degree of strong metal-support interaction in the Ru / TiO2 system. It was found that the metal-support interaction of the catalyst was stronger at a small size, which was more conducive to carbon chain growth (Nat. Commun. 2020, 11 (1), 3185). At the same time, they also found that different Ru / TiO2 catalysts can be obtained by changing the reduction temperature of the Ru / TiO2 catalyst. x Interface structure, the structure of TiO x The covering layer can directly participate in the dissociation of the CO bond, which is beneficial to improve the activity of the Fischer-Tropsch synthesis reaction (ACS Catal. 2020, 10, 12967). Patent CN 111686722 A uses an in-situ reduction method to achieve the direct reduction of the active component ruthenium on the surface of the carrier (alumina and silicon oxide), avoiding the high-temperature reduction step in the traditional method, inhibiting the sintering of ruthenium, and obtaining a ruthenium-based catalyst with high activity and high heavy hydrocarbon selectivity.
[0004] The above studies all involve modification of metals or catalysts as a whole, but the range of adjustable properties is relatively narrow and the activity in the Fischer-Tropsch synthesis reaction still needs to be improved. Summary of the invention
[0005] The purpose of the present invention is to provide a ruthenium-based catalyst and its application in the Fischer-Tropsch synthesis reaction, so as to promote the improvement of the activity and selectivity of the target product in the Fischer-Tropsch synthesis.
[0006] In order to achieve the above object, the first aspect of the present invention provides a ruthenium-based catalyst, which comprises a modified carrier and a ruthenium element loaded in the modified carrier; wherein the modified carrier is titanium dioxide loaded with a precious metal component; and the content of the ruthenium element is 0.1 to 6.5 wt % based on the total amount of the ruthenium-based catalyst. The catalyst of the present invention can improve the activity of Fischer-Tropsch synthesis and the selectivity of the target product.
[0007] A second aspect of the present invention provides a method for preparing a ruthenium-based catalyst, the method comprising:
[0008] S1, placing the carrier in a solution containing a precious metal component for impregnation to obtain an impregnated carrier; performing a first drying and a first calcination on the impregnated carrier to obtain a modified carrier;
[0009] S2, preparing a suspension containing the modified support, and adding a ruthenium precursor salt and a reducing agent to the suspension to obtain a mixed material;
[0010] S3, centrifuging the mixed material and then washing, second drying and second roasting;
[0011] Wherein, the carrier is titanium dioxide; the first calcination is carried out in a reducing atmosphere, and the second calcination is carried out in nitrogen and / or an inert gas; and the washing includes an alcohol washing treatment.
[0012] The present invention obtains a modified carrier by pre-loading a precious metal additive on titanium dioxide and performing a calcination treatment in a reducing atmosphere, which can effectively promote the generation of hydrogen overflow on the carrier and regulate the distribution and concentration of single-electron oxygen vacancies and trivalent titanium on the carrier. The modified carrier can regulate the properties of the loaded metal active components by changing the electron transfer process between the metal and the carrier, thereby achieving the effect of improving the Fischer-Tropsch synthesis activity and the selectivity of the target product.
[0013] The third part of the present invention provides a method for Fischer-Tropsch synthesis reaction, wherein the catalyst used in the Fischer-Tropsch synthesis reaction includes the aforementioned ruthenium-based catalyst or the ruthenium-based catalyst prepared by the aforementioned preparation method.
[0014] Through the above technical scheme, the ruthenium-based catalyst of the present invention includes a modified carrier and ruthenium loaded in the modified carrier, wherein the modified carrier is titanium dioxide loaded with a precious metal component. The modified carrier of the present invention can effectively regulate the oxygen vacancies and trivalent titanium content in the carrier, thereby promoting the electron transfer process between the carrier and the metal, and by further loading the ruthenium element in the modified carrier, it can effectively promote the improvement of the activity and target product selectivity in Fischer-Tropsch synthesis.
[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0017] Figure 1 It is the EPR spectra of the catalysts of Example 1 and Comparative Examples 1-4. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] The first part of the present invention provides a ruthenium-based catalyst, which includes a modified carrier and a ruthenium element loaded in the modified carrier; wherein the modified carrier is titanium dioxide loaded with a precious metal component; based on the total amount of the ruthenium-based catalyst, the content of the ruthenium element is 0.1 to 6.5 wt%.
[0020] According to the present invention, based on the total amount of the ruthenium-based catalyst, the content of ruthenium may be 0.5-5.5 wt %; preferably, the content of ruthenium may be 0.5-4 wt %.
[0021] In the present invention, TiO2 is a typical reducing oxide, which easily generates different types of metal-support interactions with active metals during the reduction process, which will affect the geometric structure and electronic structure of the active site, thereby changing the performance of the Fischer-Tropsch reaction. The titanium dioxide powder used in the present invention is used as a carrier; optionally, the titanium dioxide can be selected from at least one of rutile titanium dioxide, anatase titanium dioxide and mixed crystal titanium dioxide. Exemplarily, the mixed crystal titanium dioxide can be Degussa P25.
[0022] According to the present invention, based on the total amount of the ruthenium-based catalyst, the content of the precious metal component can be 0.001-5.0wt%, preferably, the content of the precious metal component is 0.005-1.5wt%; optionally, the precious metal element in the precious metal component is one or more metals selected from Group VIII metals and Group IB metals; preferably, the precious metal element in the precious metal component is selected from one or more of palladium, platinum, gold, silver and rhodium.
[0023] The second part of the present invention provides a method for preparing a ruthenium-based catalyst, the method comprising:
[0024] S1, placing the carrier in a solution containing a precious metal component for a first impregnation to obtain an impregnated carrier; performing a first drying and a first calcination on the impregnated carrier to obtain a modified carrier;
[0025] S2, preparing a suspension containing the modified support, and adding a ruthenium precursor salt and a reducing agent to the suspension for a second impregnation to obtain a mixed material;
[0026] S3, centrifuging the mixed material and then washing, second drying and second roasting;
[0027] Wherein, the carrier is titanium dioxide; the first calcination is carried out in a reducing atmosphere, and the second calcination is carried out in nitrogen and / or an inert gas; and the washing includes an alcohol washing treatment.
[0028] The inventors of the present invention have discovered that when preparing a catalyst suitable for Fischer-Tropsch synthesis, in order to regulate the metal-carrier interaction, the carrier can be modified first and then the subsequent metal loading can be carried out. By changing the modification process of the carrier, the regulation of various properties can be achieved, thereby achieving the effect of changing the metal-carrier interaction and optimizing the metal Fischer-Tropsch performance.
[0029] According to the present invention, the precursor salt of ruthenium can be a soluble salt of ruthenium; the soluble salt of ruthenium can be selected from at least one of ruthenium nitrosyl nitrate, ruthenium acetylacetonate, ruthenium acetate, carbonyl ruthenium chloride, ruthenium trichloride hydrate and ruthenium trichloride; preferably, the soluble salt of ruthenium is selected from at least one of ruthenium trichloride hydrate, ruthenium acetate, ruthenium nitrosyl nitrate and ruthenium acetylacetonate.
[0030] According to the present invention, in the mixed material, the molar concentration of ruthenium element can be 0.0004-0.4 mol / L; the molar ratio of the reducing agent to the ruthenium ion can be 1-20.
[0031] According to the present invention, the reducing agent is selected from boron hydride compounds; the boron hydride compounds can be selected from sodium borohydride and / or potassium borohydride. The reducing agent used in the present invention can reduce positive ruthenium ions to zero-valent ruthenium.
[0032] According to the present invention, in the solution containing the precious metal component, the appropriate molar concentration of the precious metal component ions facilitates the loading of the precious metal component by titanium dioxide; the concentration of the precious metal component calculated as the precious metal ions may be 0.0001 to 0.1 mol / L.
[0033] According to the present invention, the solution containing the precious metal component contains at least one of nitrates, acetates, sulfates, chlorides and acids of the precious metal component; the precious metal elements in the precious metal component are selected from one or more of Group VIII metals and Group IB metals; preferably, the precious metal elements in the precious metal component are selected from one or more of palladium, platinum, gold, silver and rhodium.
[0034] In the present invention, the reducing atmosphere can be a mixture of H2 and N2, wherein the H2 ratio can be 1 to 100%, preferably 10 to 20%, based on the total volume of the mixture; the first calcination conditions may include: a temperature of 300 to 650°C, preferably 400 to 600°C; a time of 2 to 8 hours, preferably 4 to 6 hours; the second calcination conditions may include: a temperature of 300 to 650°C, preferably 400 to 600°C; a time of 2 to 8 hours, preferably 4 to 6 hours.
[0035] In an exemplary embodiment of the present invention, in step S1, the impregnation step may include: mixing the carrier and the solution containing the precious metal component and then stirring; wherein the solid content of the mixture of the carrier and the solution containing the precious metal component is 10 to 200 g / L; the stirring may be mechanical stirring or magnetic stirring; the stirring conditions may include: a rotation speed of 200 to 1200 rpm, preferably 500 to 700 rpm; a time of 1 to 8 hours, preferably 3 to 6 hours; a temperature of 0 to 90°C, preferably 60 to 80°C; the first drying conditions may be The method comprises: a temperature of 50 to 150°C, preferably 80 to 120°C; a time of 4 to 48 hours, preferably 8 to 16 hours; in step S2, the conditions for the second impregnation may include: a temperature of 30 to 90°C, preferably 40 to 60°C; in step S3, the washing may include: subjecting the centrifuged material to water washing and alcohol washing, wherein the washing liquid for the alcohol washing is selected from at least one of methanol, ethanol and acetone; the conditions for the second drying may include: a temperature of 50 to 150°C, preferably 80 to 120°C; a time of 4 to 48 hours, preferably 8 to 16 hours.
[0036] The third part of the present invention provides a method for Fischer-Tropsch synthesis reaction, wherein the catalyst used in the Fischer-Tropsch synthesis reaction includes the aforementioned ruthenium-based catalyst or the ruthenium-based catalyst prepared by the aforementioned preparation method.
[0037] Optionally, the Fischer-Tropsch synthesis reaction comprises: mixing a catalyst with quartz sand and loading the mixture into a reactor, reducing the catalyst in situ, and introducing synthesis gas for synthesis reaction; wherein the synthesis gas comprises H2 and CO, the volume ratio of H2 to CO is 1 to 2, and the conditions of the synthesis reaction include: a temperature of 200 to 250°C, a pressure of 1.5 to 4 MPa, and a volume space velocity of 1000 to 10000 h -1 .
[0038] Optionally, the reducing gas used in the in-situ reduction is hydrogen, and the temperature of the in-situ reduction is 300-500°C.
[0039] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.
[0040] Example 1
[0041] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Degussa P25 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.1% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in a 10% H2 / N2 mixed atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.1Pt-10H.
[0042] (2) Catalyst preparation: 10 g of P25-0.1Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a sodium borohydride aqueous solution with a concentration of 10.002 mol / L was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.1Pt-10H catalyst.
[0043] Example 2
[0044] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Degussa P25 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.1% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. The obtained solid was then calcined in a N2 atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.1Pt-N.
[0045] (2) Catalyst preparation: 10 g of P25-0.1Pt-N was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.1Pt-N catalyst.
[0046] Example 3
[0047] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with anatase titanium dioxide in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.1% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in an air atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.1Pt-A.
[0048] (2) Catalyst preparation: 10 g of P25-0.1Pt-A was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.1Pt-A catalyst.
[0049] Example 4
[0050] (1) Carrier modification: The carrier modification method of this embodiment is the same as that of Example 1.
[0051] (2) Catalyst preparation: 10 g of P25-0.1Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.101 g was added. After further stirring, 1.06 mL of a 10 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 1Ru / P25-0.1Pt-10H catalyst.
[0052] Example 5
[0053] (1) Carrier modification: The carrier modification method of this embodiment is the same as that of Example 1.
[0054] (2) Catalyst preparation: 10 g of P25-0.1Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.204 g was added. After further stirring, 2.14 mL of a 10 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 2Ru / P25-0.1Pt-10H catalyst.
[0055] Example 6
[0056] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Degussa P25 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.05% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in a 10% H2 / N2 mixed atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.05Pt-10H.
[0057] (2) Catalyst preparation: 10 g of P25-0.05Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.05Pt-10H catalyst.
[0058] Example 7
[0059] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Degussa P25 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.2% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in a 10% H2 / N2 mixed atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.2Pt-10H.
[0060] (2) Catalyst preparation: 10 g of P25-0.2Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.2Pt-10H catalyst.
[0061] Example 8
[0062] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Degussa P25 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.5% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in a 10% H2 / N2 mixed atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named P25-0.5Pt-10H.
[0063] (2) Catalyst preparation: 10 g of P25-0.5Pt-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-0.5Pt-10H catalyst.
[0064] Comparative Example 1
[0065] Catalyst preparation: Take 10g of Degussa P25, add it to 1L of deionized water, stir it evenly, then add ruthenium trichloride aqueous solution with a Ru content of 0.309g, continue to stir evenly, add 3.24mL of 10.002mol / L sodium borohydride aqueous solution, then raise the oil bath temperature to 90°C, continue stirring for 3h and then stop, wash the mixture with deionized water and anhydrous ethanol by centrifugation, then put it into a vacuum drying oven and dry it at 80°C for 12h. The dried solid was calcined in a nitrogen atmosphere at 300°C in a tube furnace for 3h to obtain a 3Ru / P25 catalyst.
[0066] Comparative Example 2
[0067] (1) Carrier modification: Degussa P25 was calcined in a 10% H2 / N2 mixed atmosphere at 600°C for 6 h. The obtained carrier was named P25-10H.
[0068] (2) Catalyst preparation: 10 g of P25-10H was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.309 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-10H catalyst.
[0069] Comparative Example 3
[0070] (1) Carrier modification: Degussa P25 was calcined in a N2 atmosphere at 600°C for 6 h. The obtained carrier was named P25-N.
[0071] (2) Catalyst preparation: 10 g of P25-N was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.3 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-N catalyst.
[0072] Comparative Example 4
[0073] (1) Carrier modification: Degussa P25 was calcined in air at 600°C for 6 h. The obtained carrier was named P25-A.
[0074] (2) Catalyst preparation: 10 g of P25-A was added to 1 L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.3 g was added. After further stirring, 3.24 mL of a 10.002 mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3 h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol, respectively, and then placed in a vacuum drying oven and dried at 80°C for 12 h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3 h to obtain a 3Ru / P25-A catalyst.
[0075] Comparative Example 5
[0076] (1) Carrier modification: After preparing a solution of chloroplatinic acid hexahydrate, it was impregnated with Al2O3 in equal volumes at a temperature of 30°C for 12 hours, wherein the mass of platinum was 0.1% of the mass of the catalyst based on the total mass of the catalyst. The catalyst was dried in a forced air drying oven at a temperature of 90°C for 12 hours. Subsequently, the obtained solid was calcined in a 10% H2 / N2 mixed atmosphere at a temperature of 600°C for 6 hours. The obtained carrier was named Al2O3-0.1Pt-10H.
[0077] (2) Catalyst preparation: 10g of Al2O3-10H was added to 1L of deionized water, stirred evenly, and then a ruthenium trichloride aqueous solution with a Ru content of 0.3g was added. After further stirring, 3.24mL of a 10.002mol / L sodium borohydride aqueous solution was added. The oil bath temperature was then raised to 90°C, and stirring was continued for 3h before stopping. The mixture was washed by centrifugation with deionized water and anhydrous ethanol respectively, and then placed in a vacuum drying oven and dried at 80°C for 12h. The dried solid was calcined in a tubular furnace at 300°C in a nitrogen atmosphere for 3h to obtain a 3Ru / Al2O3-0.1Pt-10H catalyst.
[0078] Test Example 1
[0079] The catalysts prepared in Examples 1 to 8 were subjected to component detection by inductively coupled plasma emission spectroscopy (ICP), and the test results are shown in Table 1. In Table 1, "ruthenium element / wt%" represents the content of ruthenium based on the total amount of the ruthenium-based catalyst; "precious metal component / wt%" represents the content of the precious metal component based on the total amount of the ruthenium-based catalyst.
[0080] Table 1
[0081]
[0082]
[0083] Test Example 2
[0084] 1.0g of each catalyst (20-60 mesh) prepared in Examples 1 to 8 and Comparative Examples 1 to 5 was taken, mixed evenly with quartz sand of the same mesh size at a ratio of 1:20, and then loaded into a fixed bed reactor. The inner diameter of the reaction tube used was 15mm, and the length of the constant temperature zone was 60mm. The catalyst was then reduced in situ, the gas was pure hydrogen, the reduction temperature was 350°C, and the reduction time was 3h; the volume ratio of H2 and CO in the Fischer-Tropsch reaction raw gas was 2, the reaction temperature was 220°C, the reaction pressure was 2MPa, and the reaction volume space velocity was 4000h -1 The raw gas and the reaction gas phase products were analyzed online by Agilent 7890A gas chromatograph, and the liquid phase products were collected by hot trap and cold trap, separated, weighed and then analyzed offline. All performance evaluation results are shown in Table 2.
[0085] Table 2
[0086]
[0087]
[0088] It can be seen from Table 2 that the 3Ru / P25-0.1Pt-10H catalyst prepared by the method provided by the present invention exhibits excellent Fischer-Tropsch synthesis performance, and its CO conversion rate and C 5+ The selectivity is significantly higher than that of 3Ru / P25-0.1Pt-N and 3Ru / P25-0.1Pt-A.
[0089] Test Example 3
[0090] The catalysts prepared in Example 1 and Comparative Examples 1-4 were tested for single electron material signals using electron paramagnetic resonance (EPR). The test results are shown in Figure 1 .
[0091] Figure 1 It is shown that compared with the untreated catalysts 3Ru / P25, 3Ru / P25-N and 3Ru / P25-A prepared after treating the carrier with nitrogen and hydrogen, the 3Ru / P25-10H and 3Ru / P25-0.1Pt-10H catalysts not only have a higher intensity single-electron oxygen vacancy signal (g=2.01), but also have a higher proportion of trivalent titanium signal (g=1.94~1.98). This part of the bulk trivalent titanium can effectively induce electron transfer from the carrier to the loaded metal Ru, promote the increase of Ru charge density, and is beneficial to the adsorption of CO and the growth of the carbon chain. It can be seen that the treatment with reducing hydrogen and nitrogen gas is conducive to the generation of more oxygen vacancies and trivalent titanium. The change of the carrier properties can effectively adjust the catalytic performance of the active component Ru. When Pt is used as an auxiliary agent, hydrogen and nitrogen reduction can better promote the formation of oxygen vacancies and trivalent titanium. Compared with the performance of the catalyst 3Ru / P25-10H in the comparative example, the activity of the catalyst 3Ru / P25-0.1Pt-10H in the embodiment is improved, the methane selectivity is suppressed, and the heavy hydrocarbon selectivity is significantly increased.
[0092] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0093] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0094] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A ruthenium-based catalyst, characterized in that The ruthenium-based catalyst comprises a modified carrier and a ruthenium element loaded in the modified carrier; wherein the modified carrier is titanium dioxide loaded with a noble metal component; and based on the total amount of the ruthenium-based catalyst, the content of the ruthenium element is 0.1-6.5wt%.
2. The ruthenium-based catalyst according to claim 1, wherein Based on the total amount of the ruthenium-based catalyst, the content of ruthenium is 0.5-5.5wt%; preferably, the content of ruthenium is 0.5-4wt%.
3. The ruthenium-based catalyst according to claim 1, wherein The titanium dioxide is selected from at least one of rutile titanium dioxide, anatase titanium dioxide and mixed crystal titanium dioxide.
4. The ruthenium-based catalyst according to claim 1, wherein Based on the total amount of the ruthenium-based catalyst, the content of the precious metal component is 0.001 to 5.0 wt %, preferably, the content of the precious metal component is 0.005 to 1.5 wt %; Optionally, the precious metal element in the precious metal component is selected from one or more of Group VIII metals and Group IB metals; preferably, the precious metal element in the precious metal component is selected from one or more of palladium, platinum, gold, silver and rhodium.
5. A method for preparing a ruthenium-based catalyst, characterized in that: The method includes: S1, placing the carrier in a solution containing a precious metal component for a first impregnation to obtain an impregnated carrier; performing a first drying and a first calcination on the impregnated carrier to obtain a modified carrier; S2, preparing a suspension containing the modified support, and adding a ruthenium precursor salt and a reducing agent to the suspension for a second impregnation to obtain a mixed material; S3, centrifuging the mixed material and then washing, second drying and second roasting; Wherein, the carrier is titanium dioxide; the first calcination is carried out in a reducing atmosphere, and the second calcination is carried out in nitrogen and / or an inert gas; and the washing includes an alcohol washing treatment.
6. The preparation method according to claim 5, wherein: The precursor salt of ruthenium is a soluble salt of ruthenium; the soluble salt of ruthenium is selected from at least one of ruthenium nitrosyl nitrate, ruthenium acetylacetonate, ruthenium acetate, carbonyl ruthenium chloride, ruthenium trichloride hydrate and ruthenium trichloride; preferably, the soluble salt of ruthenium is selected from at least one of ruthenium trichloride hydrate, ruthenium acetate, ruthenium nitrosyl nitrate and ruthenium acetylacetonate.
7. The preparation method according to claim 5, wherein: In the mixed material, the molar concentration of ruthenium element is 0.0004-0.4 mol / L; the molar ratio of the reducing agent to the ruthenium ion is 1-20.
8. The preparation method according to claim 5, wherein: The reducing agent is selected from borohydride compounds; the borohydride compounds are selected from sodium borohydride and / or potassium borohydride.
9. The preparation method according to claim 5, wherein: In the solution containing the precious metal component, the concentration of the precious metal component calculated as precious metal ions is 0.0001 to 0.1 mol / L.
10. The preparation method according to claim 5 or 9, wherein: The solution containing the precious metal component contains at least one of nitrates, acetates, sulfates, chlorides and acids of the precious metal component; the precious metal element in the precious metal component is selected from one or more of Group VIII metals and Group IB metals; preferably, the precious metal element in the precious metal component is selected from one or more of palladium, platinum, gold, silver and rhodium.
11. The preparation method according to claim 5, wherein: The reducing atmosphere is a mixture of H2 and N2, wherein the proportion of H2 is 1 to 100%, preferably 10 to 20%, based on the total volume of the mixture; the first calcination conditions include: a temperature of 300 to 650°C, preferably 400 to 600°C; a time of 2 to 8 hours, preferably 4 to 6 hours; The conditions for the second calcination include: a temperature of 300 to 650° C., preferably 400 to 600° C.; and a time of 2 to 8 hours, preferably 4 to 6 hours.
12. The preparation method according to claim 5, wherein: In step S1, the first impregnation step includes: mixing the carrier and the solution containing the precious metal component and stirring; wherein the solid content of the mixture of the carrier and the solution containing the precious metal component is 10 to 200 g / L; the stirring is mechanical stirring or magnetic stirring; the stirring conditions include: a rotation speed of 200 to 1200 rpm, preferably 500 to 700 rpm; a time of 1 to 8 hours, preferably 3 to 6 hours; a temperature of 0 to 90° C., preferably 60 to 80° C.; The first drying conditions include: a temperature of 50 to 150° C., preferably 80 to 120° C.; a time of 4 to 48 hours, preferably 8 to 16 hours; In step S2, the second impregnation conditions include: a temperature of 30 to 90°C, preferably 40 to 60°C; In step S3, the washing treatment includes: subjecting the centrifuged material to water washing treatment and alcohol washing treatment, wherein the washing liquid of the alcohol washing treatment is selected from at least one of methanol, ethanol and acetone; The second drying conditions include: a temperature of 50 to 150° C., preferably 80 to 120° C.; and a time of 4 to 48 hours, preferably 8 to 16 hours.
13. A method for Fischer-Tropsch synthesis reaction, characterized in that: The catalyst used in the method includes the ruthenium-based catalyst described in any one of claims 1 to 4 or the ruthenium-based catalyst prepared by the preparation method described in any one of claims 5 to 12.
14. The method according to claim 13, wherein: The method comprises: mixing a catalyst with quartz sand and loading the mixture into a reactor, reducing the catalyst in situ, and then introducing synthesis gas to perform a synthesis reaction; The synthesis gas includes H2 and CO, the volume ratio of H2 to CO is 1-2, and the conditions of the synthesis reaction include: temperature of 200-250°C, pressure of 1.5-4MPa, volume space velocity of 1000-10000h -1 .
15. The method according to claim 14, wherein: The reducing gas used in the in-situ reduction is hydrogen, and the temperature of the in-situ reduction is 300-500°C.
Citation Information
Patent Citations
Ruthenium-based Fischer-Tropsch synthesis catalyst as well as preparation method and application thereof
CN111686722A
